GAMBARAN PENGETAHUAN SIKAP DAN PRAKTIK IBU DALAM MENYEDIAKAN KONSUMSI SAYUR PADA ANAK USIA SEKOLAH DASAR DI SEMARANG TAHUN 2016 - Livia Nur Ghassani; Ronny Aruben; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
One of the foodstuffs that are essential to obtain the balance of food consumption is a vegetable. Vegetable consumption in children of school age is still very low. According to the FAO in 2010 only 63.3% of primary school age children in Indonesia who consume vegetables. Low vegetable consumption in children can lead to decreased endurance and constipation. Mothers may affect the food choices of children by providing specific food including vegetables. This study aims to describe the knowledge, attitudes and practices of mothers in providing vegetable consumption in children of the primary school in Semarang in 2016. This type of research is descriptive qualitative research with in-depth interviews. Subjects of this study amounted to 10 key informants in SD N Jabungan and 10 key informants in SD N Pendrikan Lor 03, as many as 22 people as informants triangulation which includes 20 children and two PKK. The results of the study informants in SD N Pendrikan Lor 03 has a good knowledge compared with an informant in SD N Jabungan. More than half of the informants in SD N Jabungan have a negative attitude while in SD N Pendirikan Lor 03 having a positive attitude. Practice informants in SD N Jabungan in a vegetable serving an average of 1-9 times / week. The vegetables were served less diverse and vegetable processing methods performed by the informant was still lacking. Informants in SD N Pendrikan Lor 03 in a vegetable serving an average of 10-14 times / week. Vegetable processing methods are still lacking, but in this case, the informant was much more creative in presenting vegetables for her son if it is difficult to consume vegetables is by making innovation.